Chemical oscillation at the grain boundary of aliovalently-doped solid-oxide electrolytes. (November 2022) - Bandi, Bharathi; Chatterjee, Abhijit
Abstract: The ionic conductivity of polycrystalline aliovalently-doped solid oxide electrolytes is generally lower than that of the corresponding single-crystal material by a few orders of magnitude. This behavior arises due to slow ionic movement in the space-charge region at the grain boundary (GB). Although traditionally the Guoy-Chapman (G-C) and Mott-Shottky (M-S) models have been used to explain the nature of the space charge layer and ionic conduction at GB, these models tend to ignore the chemical interactions and the molecular scale-atomic structure at the GB. To highlight the importance of chemical interactions and GB misorientation, we systematically probe the space-charge layers at Σ 5 and Σ 13 GBs in two commonly-used solid electrolyte materials, namely, yttria stabilized zirconia (YSZ) and gadolinium doped ceria (GDC). Using molecular dynamics (MD), we provide first evidence of chemical oscillation in the O 2− ion concentration profile in the space charge region. These oscillations arise from the competing chemical, electrostatic and elastic interactions, which is missed by the G-C and M-S models. Space charge layer characteristics in each of the GBs studied is found to be different. An alternate theory which explains the chemical oscillations in the space-charge layer is presented. Implications on the ionic conduction are discussed. Graphical abstract: Image, graphical abstract